2009
DOI: 10.3727/096368909788534951
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Bone-Marrow Mononuclear Cell Transplantation after Acute Myocardial Infarction: Comparison of Two Delivery Techniques

Abstract: The objective of this study was to investigate safety and feasibility of autologous bone marrow mononuclear cells (BMMNC) transplantation in ST elevation myocardial infarction (STEMI), comparing anterograde intracoronary artery (ICA) delivery with retrograde intracoronary vein (ICV) approach. An open labeled, randomized controlled trial of 30 patients admitted with STEMI was used. Patients were enrolled if they 1) were successfully reperfused within 24 h from symptoms onset and 2) had infarct size larger than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 19 publications
(26 reference statements)
5
61
0
Order By: Relevance
“…This confirms reported literature results indicating that intracoronary injection of bone marrow-derived cells is not arrhythmogenic (11,(14)(15)(16)24).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This confirms reported literature results indicating that intracoronary injection of bone marrow-derived cells is not arrhythmogenic (11,(14)(15)(16)24).…”
Section: Discussionsupporting
confidence: 82%
“…Since the pioneering work of Strauer et al (27), many groups have performed phase I/II trials showing the intracoronary delivery of autologous marrow cells to be safe and potentially effective (16,26,27). Larger randomized trials have confirmed the efficacy of this new therapy (28)(29)(30), although these results have been disputed (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was designed to answer questions on the release techniques and the consequent distribution of cells 19 . Its small sample size and its open-label nature prevent us from reaching definitive conclusions when evaluating subgroups 20 .…”
Section: Moreira Et Al Stem-cell Injection After Amimentioning
confidence: 99%